2011
DOI: 10.1111/j.1748-1716.2011.02259.x
|View full text |Cite
|
Sign up to set email alerts
|

Granulocyte colony-stimulating factor stabilizes cardiac electrophysiology and decreases infarct size during cardiac ischaemic/reperfusion in swine

Abstract: G-CSF increases the DPT, ERP and VFT and reduces the infarct size, thus stabilizing the myocardial electrophysiology, and preventing fatal arrhythmia during I/R. The protective mechanism could be via its effect in preventing cardiac mitochondrial dysfunction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 39 publications
1
19
0
Order By: Relevance
“…[28][29][30] Several studies demonstrated the beneficial effects of pharmacological interventions on cardiac electrophysiological alterations, such as decreased VF incidence and prolonged time to the first occurrence of VF during I/R. 25,26 However, this is the first study to demonstrate the effect of p38 MAPK inhibitor, SB203580, on cardiac arrhythmias during myocardial I/R in an in vivo rat model. In I/R rats, SB203580 given before or during ischemia decreased the incidence of VT/VF and the arrhythmia scores, whereas SB203580 given at the onset of reperfusion did not protect the heart from arrhythmia during I/R.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…[28][29][30] Several studies demonstrated the beneficial effects of pharmacological interventions on cardiac electrophysiological alterations, such as decreased VF incidence and prolonged time to the first occurrence of VF during I/R. 25,26 However, this is the first study to demonstrate the effect of p38 MAPK inhibitor, SB203580, on cardiac arrhythmias during myocardial I/R in an in vivo rat model. In I/R rats, SB203580 given before or during ischemia decreased the incidence of VT/VF and the arrhythmia scores, whereas SB203580 given at the onset of reperfusion did not protect the heart from arrhythmia during I/R.…”
Section: Discussionmentioning
confidence: 98%
“…23 The infarct area (TTC negative) and the nonischemic area (Evans blue-stained area) were determined by the ImageTool software version 3.0. The infarct size was calculated depending on the weight of each slice according to the formula of Reiss et al [24][25][26] Western Blot Analysis At the end of each experiment, the heart was rapidly excised, and then the whole ventricular tissue was collected, quickly frozen in liquid nitrogen, and stored at 2808C until analysis. Heart proteins were lysed with extraction buffer (20 mmol/L Tris-HCl, 1 mmol/L Na 3 VO 4 , 5 mmol/L NaF) and separated by electrophoresis on 10% or 15% sodium dodecyl sulfate-polyacrylamide gel electrophoresis and then were transferred onto a polyvinylidene difluoride (PVDF) membranes.…”
Section: Infarct Size Determinationmentioning
confidence: 99%
“…, Kanlop et al . , Zang et al . ) and that the dysfunction of cardiac mitochondria has been shown to cause both arrhythmias as well as ventricular dysfunction (Clements‐Jewery , Brown & O'Rourke , Palee et al .…”
Section: Discussionmentioning
confidence: 99%
“…described that granulocyte colony‐stimulating factor (G‐CSF) given prior to LAD ligation increases heart function and decreases infarct size (Kanlop et al . ). Combination of l ‐arginine with ischaemic post‐conditioning protects the pig heart against ischaemia and reperfusion injury (Gonon et al .…”
Section: Common Rodent Models Of Ischaemia or Non‐ischaemic Hypoperfumentioning
confidence: 97%